Recent progress on curcumin-based therapeutics: a patent review (2012-2016). Part II: curcumin derivatives in cancer and neurodegeneration. (3rd August 2017) - Di Martino, Rita Maria Concetta; Bisi, Alessandra; Rampa, Angela; Gobbi, Silvia; Belluti, Federica
ABSTRACT: Introduction : Curcumin, the main bioactive compound found in the rhizome of Curcuma longa L., is considered a 'privileged structure', due to its ability to modulate different signaling pathways involved in the pathogenesis of several diseases. Unfortunately, its poor pharmacodynamic and pharmacokinetic properties, mainly related to chemical instability, low solubility and rapid metabolism, greatly reduce its therapeutic potential. In the last years a number of derivatives were developed and patented, aimed both at improving its multifaceted biological profile and overcoming its undesired effects. Areas covered : This review summarizes the patent literature of the last five years dealing with synthetic curcumin-related compounds in cancer and neurodegeneration, properly designed in order to avoid the so-called 'dark side of curcumin', and to take advantage of the beneficial properties of this molecule, worth to be further exploited to obtain effective therapeutics. Expert opinion : Due to the synergistic binding to several networked targets, curcumin turned out to be suitable for polypharmacological approaches, and its 'privileged structure' could also provide the key scaffold to develop novel multipotent drugs useful for treating multifactiorial pathologic conditions such as cancer and neurodegeneration.